Proposals Annual Plan 1968-69 Punjab State - Planning Commission (Planning Commission, 1968)
For sustained economic growth, which is an essential feature of planned development. the outlay and programme for each annual Plan must necessarily be related to the dimensions set for the Five Year Plan. After detailed scrutiny and keeping in view the constraint of resources on one hand and the minimum needs of development on the other, it has been accepted by the Planning Commission that the outlay for the Fourth Five Year Plan—Punjab, could not be reduced to below Rs 280 crore. the economic recession, which has befallen the country as a result of severe drought over two successive years, has created uncertainty whether it would be possible to sustain the outlays envisaged earlier for the Fourth Plan.
Planning Department, Punjab Chandigarh